What is youth political participation?: literature review on youth political participation and political attitudes - Weiß, Julia (Frontiers in political science, 2020)
Looking at political participation behavior of young adults in contemporary Europe this paper provides the reader with a map of different terminologies and logics that are used to discuss youth political participation. The existing literature is examined using five guiding questions: what defines youth political participation? How does youth political participation differ from adult political participation? How do young adults develop political attitudes? What methods are being used to analyze youth political participation? How does youth political participation research differ across Europe? For those who are dealing with the topic of youth political participation for the first time, this offers a unique opportunity to get an overview. At the same time, already well-informed researchers are given the opportunity to reflect on the current state of research in this field. Finally, the article points out where future research in the field is needed.
Gesehen am 26.09.2020